Comparing the Quality of Media Coverage in Democratic Elections - Leicht, Hannah (My University, 2015)
This research study looks to determine the varying quality of election coverage in democratic nations. Articles from USA Today and The New York Times that covered the 2012 presidential election were used to study media quality in the United States, The Daily Telegraph and The Guardian provided coverage of the 2010 British election, and The National Post and The Globe and Mail were used to examine coverage of the 2011 Canadian election. The articles chosen from these newspapers provided election coverage from one month before the respective election days. A comprehensive list of terms and phrases denoting high or low quality media coverage was used to compare the quality of the newspapers from each nation. The findings of this research showed that Canada had the highest quality media while Great Britain had the lowest. All three countries had similar percentages for low quality terms.
Keywords: Democratic; Election; Coverage